A Case Study on the Failure of International Human Rights Law to Protect Minority-Belief Students in Educational Institutions - Rehman, Naveed ur; Niazi, Farooq Umair; Khan, Shakil Ahmad; Rehman, Asma (Law and Policy Review, 2025)
This article critically examines the shortcomings in human rights law that hinder the protection of Freedom of Religion or Belief (FoRB) for students of minority beliefs in educational institutions. While international legal frameworks, such as the Universal Declaration of Human Rights, the International Covenant on Civil and Political Rights, and the European Convention on Human Rights, nominally protect these freedoms, their practical realization remains different. Case analyses and judgments, including Lautsi and Others v. Italy (2011) and Osmanoğlu and Kocabaş v. Switzerland (2017), have revealed systemic failures such as discriminatory policies and inadequate approaches to accommodate religious practices. This research emphasizes that curricula reflect dominant cultural narratives while marginalizing students from minority belief systems through biased curricula, restrictive dress codes, and a lack of grievance mechanisms. Moreover, opt-out provisions meant to honor religious diversity often stigmatize minority students and do not provide for non-believers. This research recommends the introduction of inclusive curricula, Opt-out possibilities, opt-in approaches to religious education, and robust accountability systems to uphold FoRB protections. To address this issue, this study proposes that a transnational, multi-stakeholder process involving governments, religious scholars, education sectors, and international agencies. Such collaboration is essential to promote fair access to FoRB for all students in ways that encourage pluralism and social cohesion.